Letter (copy) : International Brigade Dependants and Wounded Committee - Citrine, Walter, 1887-1983
034-0153-001 Secretary's. WMC/FC/EK/1751. 30th August, 1938. Mr. R. Prain, Electrical Trades Union, 11, Macaulay Road, Clapham Common, London, S.W.4. Dear Mr. Prain, International Brigade Dependants and Wounded Aid Commttee. I have your letter of the 29th instant on the above subject. When I wrote to you last on this matter we were anticipating that we would be supplied by the Committee with certain necessary particulars. We were later informed that the accounts were in the course of audit and although nearly three months have passed we have heard nothing further from them. Under the circumstances, the matter will not come up for consideration again until the particulars have been received. The second paragraph of my letter of the 4th July refers to one of the difficulties encountered when the matter was considered about twelve months ago. Should any development occur I will again communicate with you, but in the meantime I hope you will not hold up the decision of your Executive in regard to their support of the International Solidarity Fund. Yours sincerely, General Secretary. 292/946/34/153